2011
DOI: 10.1186/1471-2458-11-597
|View full text |Cite
|
Sign up to set email alerts
|

Explaining gender differences in non-fatal suicidal behaviour among adolescents: a population-based study

Abstract: BackgroundWhile suicide is the second leading cause of death among young people in most industrial countries, non-fatal suicidal behaviour is also a very important public health concern among adolescents. The aim of this study was to investigate gender differences in prevalence and emotional and behavioural correlates of suicidal behaviour in a representative school-based sample of adolescents.MethodsA cross-sectional design was used to assess suicidal behaviour and various areas of emotional and behavioural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
3
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 37 publications
11
50
3
12
Order By: Relevance
“…This can be explained by generally earlier physical and mental maturation of girls, as well as gender differences regarding emotional problems and behaviour [33]. The seasonal and weekly variations in the numbers of calls concerning children's and adolescents' suicide attempts in our study were statistically significant.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This can be explained by generally earlier physical and mental maturation of girls, as well as gender differences regarding emotional problems and behaviour [33]. The seasonal and weekly variations in the numbers of calls concerning children's and adolescents' suicide attempts in our study were statistically significant.…”
Section: Discussionsupporting
confidence: 47%
“…The severe toxic/lethal doses were almost two times more common for males than for females. It is known that males generally have a stronger suicidal intent than females [40], and this gender feature can be observed not only in adult suicides, but also in children and adolescents [33,41]. Only one in five poisoned patients received qualified medical care within 1 hr after drug ingestion, that is, within the period ideal for early primary elimination measures (gastric lavage, activated charcoal administration, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent females have greater emotional intensity and more strong emotional reactions to social stimuli, as compared to males, and they also have higher levels of depression (Charbonneau et al 2009;Hyde et al 2008). Additionally, adolescent females are more likely to report suicidal thoughts and attempts than are adolescent males (Kaess et al 2011;Wunderlich et al 2001). According to Kaess et al (2011), one explanation for this gender difference is that adolescent females reported higher levels of internalizing problems and adolescent males reported higher levels of externalizing problems.…”
Section: Gender Victimization and Suicidementioning
confidence: 99%
“…Additionally, adolescent females are more likely to report suicidal thoughts and attempts than are adolescent males (Kaess et al 2011;Wunderlich et al 2001). According to Kaess et al (2011), one explanation for this gender difference is that adolescent females reported higher levels of internalizing problems and adolescent males reported higher levels of externalizing problems. In other words, adolescent males are more likely to act with outward displays of aggression while adolescent females are more likely to turn their aggression inward.…”
Section: Gender Victimization and Suicidementioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited. ders (7,14,15). Also, suicide attempt differs between males and females with psychiatric disorders (14).…”
Section: Introductionmentioning
confidence: 99%